The Total Defense Concept as the Embodiment of Sweden’s Strategic Culture - N. E. Belukhin; V. V. Vorotnikov; S. Y. Dianina (Vestnik MGIMO-Universiteta)
The article deals with the «total defense» concept considering it to be part of Sweden’s strategic culture and provides an overview of how this concept defines Sweden’s approach towards the defense cooperation within the EU. «Total defence» remains staple in the Swedish defence planning and the perception of risks to national security, but has not yet received sufficient attention from Russian researchers. The announced restoration of the effective total defense system potentially comparable to that of the period of bipolar confrontation is associated with significant difficulties due to the gradual reduction in defense spending after the end of the Cold War and the decentralization of the national crisis preparedness structures which was initiated in the early 2000s. The total defense itself also reveals tensions between the demands for consolidation and centralized decision-making and the liberal, open nature of the Swedish society and national economy, as well as the principles of responsibility, subsidiarity and similarity that underline the present Swedish emergency response system. The total defense, is, therefore, regarded as an attempt at creating an effective crisis preparedness system that would function successfully in a democratic society, both under the conditions of peace and potential armed conflict, without the need to declare an emergency and endow individual bodies or a selected group of individuals with exclusive powers. The Swedish strategic culture, therefore, stipulates that it is important not only to resolve a crisis effectively, but also to do so in a way which would not endanger the regular functioning of political institutions and the rule of law. Within the EU Sweden has earned credit for developing civilian or non-military elements of crisis management, while «more hardware» defense cooperation within PESCO and the European Defense Fund is defined by the pragmatic economic interests of Swedish defense companies rather than by strategic considerations. The Swedish Experience with «total defence» will continue to face the same dilemma – the need to rebuild a robust and self-reliant national defence while preserving the liberal principles in politics as well as in economy.